Take control of what's new in Word 2004 : advanced editing & formatting - Neuburg, Matt (Peachpit Press, 2007)
Work more effectively on your Mac by learning nitty-gritty details about Word 2004's new features! Under Matt Neuburg's expert guidance, you'll get help with the complex changes in Word's editing and formatting features. You'll learn the hidden rules that govern smart buttons and animated blue underlines and find out how to take advantage of new style features, including table and list styles. Matt also explains how to type special characters and teaches you three techniques for entering frequently used characters . Anyone relying on Unicode or unusual fonts needs Matt's real-world help and explanation of why fonts may not work as expected, including four solutions to common problems with old fonts . Finally, Matt explains in detail how you can use the new comment and revision tracking features most effectively. Companion volume! This ebook is the second of a two-volume set. The 73-page Take Control of What's New in Word 2004 helps with installation (including advice on handling the 80 fonts that Word installs); looks at what's new with AppleScript; and explains the Navigation pane, the Toolbox, and Notebook view.